THERMO-CHEMICAL REACTIONS AND STRUCTURAL EVOLUTION OF ACRYLAMIDE-MODIFIED POLYACRYLONITRILE - Wu, Xue-ping; Zhang, Xian-long; Lu, Chun-xiang; Ling, Li-cheng (Chinese journal of polymer science, 2010)
Thermal properties of acrylonitrile （AN）-acrylamide （AM） copolymers for carbon fibers were studied by DSC and in situ FTIR techniques in nitrogen （N2） and air flows. The cyclization mechanism and stabilization behavior of polyacrylonitrile （PAN） were discussed. In N2 flow, it was found that AM had the ability to initiate and accelerate cyclization process, which was confirmed by the fact that the initiation of nitriles shifted to a lower temperature. Compared to AN homopolymer, the initiation temperature of cyclization was ahead 32 K by introducing 3.59 mol% AM into the copolymer. The exothermic reaction was relaxed due to the presence of two separated exothermic peaks. Accompanied by DSC, in situ FTIR and calculation of activation energy, the two peaks were proved to be caused by ionic cyclization and free radical cyclization, respectively, and the corresponding cyclization mechanism was proposed. With increasing in AM content, the ionic cyclization tends to be dominant and the total heat liberated first increases and then decreases. For AN homopolymer, the activation energy of cyclization is 179 kJ/mol. For AN-AM copolymer （containing 3.59 mol% AM）, the activation energy of ionic cyclization is 96 kJ/mol and that of free radical cyclization is 338 kJ/mol. In air flow, similar cyclization routes occur and the difference is the contribution of oxidation. The oxygen in environment has no remarkable effect on cyclization of AN homopolymer but retards the cyclization of AN-AM copolymers. For AN-AM copolymer with 3.59 mol% AM, the cyclization temperature is postponed 10℃ in air.